Effects of Montessori-Based Stimulation on Fine and Gross Motor Development Among Children with Stunting: A Quasi-Experimental Study - Tukimin bin Sansuwito; Rini Anggeriani; Rinda Lamdayani; Ade Marlisa Rahmadayanti; Aris Citra Wisuda; Indah Rahmadaniah (Jurnal Keperawatan Indonesia, 2026)
Stunting affects not only physical growth but also several aspects of child development, including gross and fine motor skills. Early stimulation interventions, such as Montessori-based activities, have been proposed to enhance developmental outcomes through structured sensorimotor experiences. This study aimed to evaluate the effects of Montessori-based stimulation on motor development among children with stunting and to compare its outcomes with those of conventional stimulation. A quasi-experimental study with intervention and control groups was conducted among 120 children with stunting aged 36–59 months. Participants were allocated to either a Montessori group (n = 60) or a conventional stimulation group (n = 60). The intervention was delivered over 12 weeks, three times per week, with each session lasting 60 minutes. Gross and fine motor development were assessed before and after the intervention using the Pre-Screening Developmental Questionnaire. Within-group changes were analyzed using the Wilcoxon signed-rank test, while between-group differences were examined using the Mann–Whitney U test. The Montessori group showed significant improvements in gross motor development (p = 0.028) and fine motor development (p = 0.003). In the conventional group, only fine motor development improved significantly (p = 0.046), whereas changes in gross motor development were not statistically significant (p = 0.144). However, no significant differences were observed between the Montessori and conventional groups in post-intervention comparisons (p > 0.05). Montessori-based stimulation may contribute to improvements in gross and fine motor development among children with stunting. However, the absence of significant between-group differences suggests that Montessori-based stimulation was not superior to conventional stimulation during the study period. Further studies with larger samples and randomized controlled designs are needed to clarify its role in supporting developmental outcomes in children with stunting.